КӘМИЛ ИНСАН ТӘРБИЯСЫ – МИЛЛИЙ ИДЕЯНЫҢ БАСЛЫ МАҚСЕТИ - Абаев, С.; Якубов, М.А.; Алламбергенов, Е.К. (SCIENCE and SOCIETY, 2021)
The article examines various aspects of the essence of the content of the concept of "ideal person", shows the need for such a person for society. Based on the works of the President of the Republic of Uzbekistan Shavkat Mirziyoyev, various measures taken to educate a perfect person in our country are analyzed.
Keywords: society; spirituality; education; people; intelligent person; personality